ELECTRONIC ID CARD (KTP-EL) SERVICE INNOVATION THROUGH THE PETA CINTA PROGRAM IN SUMBERSARI SUB-DISTRICT, JEMBER REGENCY - Ananta Riefnaldo Maliki; Raden Imam Al Hafis (Yayasan Wayan Marwan Pulungan, 2026)
This study aims to evaluate the implementation of the electronic ID card (KTP-el) service innovation through the Peta Cinta program (Pelayanan Tuntas Cetak KTP-el di Kecamatan / Complete Sub-district E-KTP Printing Service) in Sumbersari District, Jember Regency. Developed by the Jember Regency Government through the Dispendukcapil (Department of Population and Civil Registration), this program serves as a public service innovation designed to expand access to e-KTP printing at the sub-district level. This research focuses on assessing the alignment between Standard Operating Procedures (SOPs) and actual field operations, as well as identifying various technical and administrative constraints affecting public service effectiveness. Utilizing a qualitative research method with a descriptive approach, this study draws on secondary data sources, including official Dispendukcapil documents, Government Institution Performance Accountability Reports (LAKIP), Central Bureau of Statistics (BPS) data, scientific journals, news articles, and regulations related to population administration. Data was gathered through documentation and literature studies, and subsequently analyzed using qualitative descriptive analysis techniques. The findings indicate that the Peta Cinta program is a progressive public service innovation capable of bringing e-KTP printing services closer to the community by expanding service points across sub-districts. This innovation supports the digital transformation of public services through integration with the J-SIP application and IT-based service concepts. Nevertheless, the program's effective implementation still faces several field challenges. The primary obstacles identified include logistical limitations such as ink, ribbons, and e-KTP blanks, internet network disruptions, printer malfunctions, and uneven technical capabilities among sub-district personnel regarding equipment maintenance.